Edmunds United States Coin Prices: Comprehensive Current Market Prices for all U.S. Coins - Belloch, Robert I. (Edmund EDmunds, 1987)
United States Coin Prices. This book is intended to be a useful guide for collectors of United States coins as well as the investor who wishes to include rare U.S. coins in his investment portfolio. At the time that this book is being written, the entire U.S. coins series is experiencing a dramatic upswing in prices.
Keywords: Economics